Disability, work status and deprivation among working age-group: shred of evidences from National Sample Survey 76th round data - Gupta, Jagriti; Govil, Dipti; Singh, Angad (International Journal Of Community Medicine And Public Health, 2024)
Background: In the Indian context, where a substantial portion of the population is of working age and 2.1% grapple with disabilities, as per the 2011 census, the emergence of diverse disability profiles within this demographic becomes a paramount concern. This issue holds profound consequences, directly impacting the nation’s productivity and overall economic landscape. The focus of this study is a comprehensive examination of the repercussions of disability, honing in on the alteration and loss of occupational experiences among individuals in the working-age stratum. Methods: The primary objective is the computation of a "disability deprivation index" for both India as a whole and its states, a multinomial logistic regression model is employed, seeking to elucidate the extent of the impact precipitated by the onset of disability in the working-age population. Multiple classification analysis is integral to determining adjusted percentages (probabilities) of changes of work, loss of work, and no loss or change of work, derived from multinomial logit regression, fostering a nuanced understanding of the issue. Results: The study reveals that 2.2% of individuals previously gainfully employed experience disability, with a significant majority losing their livelihoods due to disabling conditions. The disability deprivation index provides insights into relative deprivation levels across states, highlighting Kerala as the least deprived and Bihar as the most deprived. Conclusions: Despite commendable efforts by government and non-governmental organizations to address the needs of disabled population, the study underscores the stark reality that these provisions reach only a fraction of the disabled population, intensifying the severity of the situation concerning disability in India.